2018
DOI: 10.1002/jez.2184
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of lamp spectrum to quantify ecological effects of light at night

Abstract: For many decades, the spectral composition of lighting was determined by the type of lamp, which also influenced potential effects of outdoor lights on species and ecosystems. Light-emitting diode (LED) lamps have dramatically increased the range of spectral profiles of light that is economically viable for outdoor lighting. Because of the array of choices, it is necessary to develop methods to predict the effects of different spectral profiles without conducting field studies, especially because older lightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
115
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 48 publications
2
115
0
4
Order By: Relevance
“…This shift towards exposure to short‐wavelength light has caused concern for human health (West et al., ) and ecological systems (Davies et al., ). Known ecological responses to light at night vary in their sensitivity to different wavelengths, although many responses appear to be more sensitive to “blue” light (Longcore et al., ). Our results suggest that the response of an ecosystem to changes in the intensity and spectra of artificial light in the environment may be complex and mediated through multiple physiological pathways and trophic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift towards exposure to short‐wavelength light has caused concern for human health (West et al., ) and ecological systems (Davies et al., ). Known ecological responses to light at night vary in their sensitivity to different wavelengths, although many responses appear to be more sensitive to “blue” light (Longcore et al., ). Our results suggest that the response of an ecosystem to changes in the intensity and spectra of artificial light in the environment may be complex and mediated through multiple physiological pathways and trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that great care should be taken to consider both the physiological and ecological pathways through which the impacts of artificial light are realized. Plants, and hence specialist herbivores, are likely to be susceptible to higher wavelength light, particularly the red/far red ratio (Bennie et al., ; Briggs, ; Cathey & Campbell, ), while many physiological pathways such as cryptochrome and melatonin, and behaviours such as insect phototaxis are most sensitive to lower wavelength blue light (Longcore et al., ). Species that are able to utilize artificial light for vision, are likely to respond to broad wavelength “white” light.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to blue light at night is known to cause insomnia and increased disease risk in humans (American Medical Association, ). However, the effects of this widespread spectral shift on other organisms have only recently attracted the attention of researchers (Davies et al, ; Donners et al, ; Gaston, Visser, & Hölker, ; Justice & Justice, ; Lewanzik & Voigt, ; Longcore et al, ; Pawson & Bader, ; Plummer, Hale, O'Callaghan, Sadler, & Siriwardena, ; Somers‐Yeates, Hodgson, McGregor, Spalding, & Ffrench‐Constant, ; Spoelstra et al, ; van Grunsven et al, ; van Langevelde, Grunsven, Veenendaal, & Fijen, ; Wakefield, Broyles, Stone, Jones, & Harris, ).…”
Section: Introductionmentioning
confidence: 99%
“…() and Longcore et al . () have devised theoretical models to determine how specific light sources overlap with the full range of visual sensitivities for organisms. These studies have established an understanding of how different spectra of light sources overlapped with different visual systems, however, these studies combine the overall visual range of organisms and do not investigate artificial light at the photoreceptor level.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have investigated behavioral responses to different light sources (Langevelde et al, 2011;van Grunsven et al, 2014;Longcore et al, 2015;Spoelstra et al, 2017), few studies have investigated varied spectral signatures in the environment, see Davies et al (2013); Donners et al (2018); Longcore et al (2018). Davies et al (2013) found that low-pressure sodium lamps emitted the smallest proportion of the light spectrum to which animals are sensitive, whereas metal halides (MH) lamps emitted the largest proportion.…”
Section: Introductionmentioning
confidence: 99%